2010
DOI: 10.1111/j.1751-7176.2009.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Therapy in African Americans: Findings From an Inner‐City Ambulatory Clinic

Abstract: African Americans bear a greater burden of hypertension. Understanding prevailing epidemiologic patterns can facilitate the implementation and successful outcome of community programs. The authors assessed practice patterns of antihypertensive drug utilization and blood pressure (BP) control in a predominantly African American population in Brooklyn, NY, from January 1 to January 31, 2008. A total of 416 (53.1%) had hypertension, with a mean age of 61 years, and 267 (64%) were women. In general, 212 (50.9%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Babesia canis infection induced cardiac disorders in dogs with 32% of AV block [33]. Two reports showed myocardial damage and serious arrhtymia associated with severe babesiosis in two American patients [34,35]. A recent report showed that 19.6% of hospitalized American patients with acute babesiosis due to B. microti developed cardiac complications, mostly atrial fibrillation, heart failure, QT interval prolongation and cardiac ischemia [36].…”
Section: Discussionmentioning
confidence: 99%
“…Babesia canis infection induced cardiac disorders in dogs with 32% of AV block [33]. Two reports showed myocardial damage and serious arrhtymia associated with severe babesiosis in two American patients [34,35]. A recent report showed that 19.6% of hospitalized American patients with acute babesiosis due to B. microti developed cardiac complications, mostly atrial fibrillation, heart failure, QT interval prolongation and cardiac ischemia [36].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of treated black patients in an ambulatory clinic found that 39% reported receiving a diuretic. 7 One would expect that among black patients with uncontrolled hypertension, the proportion prescribed a diuretic would be higher. In this context, the 46% reported in this study has to be considered strikingly low and adds to the evidence that use of diuretics seems to be suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite the reported efficacy for use of thiazide diuretics and potassium-sparing diuretics in blacks, 5,6 a recent study of treated black patients in an ambulatory clinic found that only 39% of patients reported taking a diuretic. 7 Several large trials have reported that the cardiovascular outcome after treatment with "newer" classes of agents (angiotensin-converting enzyme inhibitors (ACEIs), angiotensin-receptor blockers (ARBs), and calcium channel blockers (CCBs) is not superior to that after treatment with the "older" diuretic agents. 8 Furthermore, the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) reported that in black patients the outcome was better after treatment with diuretics than after treatment with ACEIs.…”
mentioning
confidence: 99%
“…18 A careful examination of hypertension care of innercity African Americans was reported from Brooklyn by Dr Esosa Odigie-Okon and colleagues. 19 In assessing practice patterns in that community, these authors found that 50% of treated black patients were at their BP goals. About 60% of these patients were receiving >1 drug.…”
Section: Role Of Ethnicitymentioning
confidence: 99%